Policy initiatives for health and the bioeconomy - Borowiecki, Martin (OECD Science, Technology and Industry Policy Papers, 2019)
This document presents twelve policy initiatives supporting health and the bioeconomy from different OECD countries. The initiatives reviewed include: i) funding for public health centres that translate biomedical research into clinical research and care; ii) cross-border public-private consortia around health research and innovation; iii) strategies developed by national health agencies promoting translational research; and iv) national high-level strategies for the bioeconomy. It also provides a comparison of these initiatives with a focus on policy objectives, targets groups, sectoral priorities, budget, time horizon, selection criteria, international collaboration, and evaluation of the initiatives